Clinicians and the economic evaluation of health - Merino José G (Instituto Nacional de Salud Pública, 2002)
Papers dealing with the economic evaluation of health care have proliferated in the clinical literature. They provide an evidence-based element to help policy makers allocate resources among competing projects. These studies are generally done from a the perspective of a health provider (public or practice) or a public health professional, they do not take into account the special nature of the patient-physician relationship. The value of these studies for a clinician caring for an individual patient is questioned because the perspective used and the values measured represent those of society or a health provider, not those of patients. In addition, since cost-effectiveness analysis fails to take into account important societal ethical beliefs that are relevant to the care of individuals, its application to individual care is limited. Physicians should use these analyses when working as private or public policy makers, not as clinicians.